Spatiotemporal evolution and interaction of soil and water resource carrying capacities in Gansu Province - WANG Lichuan; SUN Dongyuan; MA Yali; WU Lanzhen; CUI Yanqiang; SHU Heping; WANG Xingfan (Guan'gai paishui xuebao)
【Objective】Gansu Province, with its unique geographic and climatic conditions, faces significant challenges in sustainable use of its soil and water resources. This paper analyzes the spatiotemporal variation interaction of soil and water resource carrying capacities in the province, with the aim of informing improved resource management and promoting sustainable development.【Method】Data on soil and water resources from 2000 to 2022 were used to assess their spatiotemporal variation and coupling coordination at the municipal and prefectural levels. The ecological footprint model and the coupling coordination degree model were applied for quantitative analysis.【Result】① Temporally, the per capita ecological footprint and carrying capacity of water resources in the province fluctuated significantly over the study period. The highest per capita water ecological footprint was 0.789 hm2 in 2004, and the lowest was 0.687 hm2 in 2019. Spatially, water resource footprints were generally higher in the northwest and lower in the southeast. ② For land resources, the per capita ecological footprint and carrying capacity first declined and then gradually increased over time. Spatially, the pattern mirrored that of water resources, with higher footprints in the northwest and lower footprints in the southeast. ③ The coupling degree between the per capita ecological footprint and the carrying capacities of soil and water resources showed a steady increase, ranging from 0.5 to 0.9. This indicates a transition from weak to moderate and strong coordination levels.【Conclusion】Enhancing the integrated management of soil and water resources, along with the implementation of region-specific protection strategies, is essential for improving carrying capacity and ensuring the sustainable use of soil and water resources in Gansu Province.